THE SLEEP QUALITY OF CONGESTIVE HEART FAILURE PATIENTS WHO EXPERIENCE DYSPNEA - Kasron; Susilawati; Wishnu Subroto (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2020)
Congestive Hearth Failure (CHF) is a terminal disease that causes a variety of very disturbing clinical manifestations such as dyspnea. Dyspnea in CHF patients can cause a sleep disorder such as Sleep-disordered breathing (SDB). The aim of study was to determine the quality of sleep in patients with congestive heart failure who experience dyspnea. The research method uses descriptive studies. Sampling method by accidental. Measurement of dyspnea with a modified Borg scale. Univariable analysis on the variables studied. The results showed that the dyspnea score was 4.2 ± 0.9, the green dyspnea category was 62.5% dominant, the most dominant sleep quality was the very poor category 56.25%. The conclusion shows that the most dyspnea category is in the green category, the dominant sleep quality is very bad, the sleep quality is very bad for male respondents as much as 77.78%, experienced by high school respondents, experienced by respondents in grade CHF III, experienced by respondents in the green dyspnea category. Further research is needed to improve sleep quality in people with CHF who experience dyspnea.